Insights into elusive and cooperative multi-oxidant mechanisms in enabling catalytic methane-to-methanol conversion over atomically dispersed metals - Zhang, Li-Long; Su, Yaqiong; Chen, Dandan; Wu, Hongguo; Xu, Feng; Li, Hu; Yang, Song (Inorganic chemistry frontiers, 2023)
NO x is frequently invoked as an oxidant for direct selective conversion of methane into methanol (DSCMM), which has long been considered one of the holy grails in green chemistry. A challenge in studying the use of NO x in oxidizing methane is the interconversion of various NO x compounds as well as the easy formation of O 2 , rendering it difficult to draw firm conclusions on the oxidant. Here, we explicitly elucidate the strengths of using dual oxidants (NO and N 2 O) for DSCMM over various phosphotungstic acid-supported single-atom catalysts. A competitive but cooperative multi-functional protocol involving dual oxidants is proposed to enhance catalytic performance due to its overall strong CH 4 adsorption and thermodynamic favorability compared with normal mechanisms (single O 2 , N 2 O, or NO). The new cooperative multi-functional mechanism strategy is expected to motivate further research to elaborate on its potential advantages in DSCMM and other relevant catalytic systems. A cooperative multi-oxidant protocol was developed to be efficient for converting greenhouse gas (CH 4 ) and environmentally polluting gases (NO x ) into clean and renewable energy molecules (CH 3 OH).